Effects of maternal handling training at home, on development of fine motor skills in the children with cerebral palsy: A randomized clinical trial. Issue 4 (1st October 2016) - Johari, Sahar; Rassafiani, Mehdi; Dalvand, Hamid; Ahmadi Kahjoogh, Mina; Daemi, Mostafa
ABSTRACT: Cerebral palsy (CP) is the most common physical disability in children. These children require long-term therapy for achieving better motor function. It seems that treatment and training at home is necessary. The purpose of this study was to determine the impact of handling training of mothers at home on fine motor skill development of children with CP. In this single-blind randomized clinical trial study, 40 children (ages 5–12 years old) with CP were recruited from some of Tehran's rehabilitation clinics based on predetermined inclusion criteria and randomly assigned to intervention groups (with handling training of mothers at home) and control (without handling training) groups. Data were collected using the Gross Motor Function Classification System, Manual Ability Classification System, and the fine-motor component of the Bruninks-Oseretsky Test of motor proficiency. Although both groups showed improvement in fine motor skill development ( p  < 0.001), improvement in the intervention group was significantly higher than in the control group ( p  < 0.001). Mothers handling training at home improved fine motor skills development of children with CP.